2015
DOI: 10.1007/s11356-015-5693-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality assessment of urban green space under long-term reclaimed water irrigation

Abstract: Reclaimed water is widely used for landscape irrigation with the benefits of saving fresh water and ameliorating soil quality. Field samples were collected from seven parks in Beijing irrigated reclaimed water with different irrigation history in 2011 and 2014 to evaluate the long-term impacts of reclaimed water irrigation on soil quality. Soil quality index method was used to assess the comprehensive effects of reclaimed water irrigation on soil. Results showed that the effects of reclaimed water irrigation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This is associated with an upsurged soil quality grade from IV to III in most soil sites treated by TWW irrigation (Figure 2), indicating a positive effect of TWW irrigation on soil quality indices calculated by nutritional/chemical indicators. Our results corroborate the findings of previous studies conducted by Chen et al [63] and Lyu and Chen [64], who found that SQI and soil health conditions were improved by TWW irrigation. Among different soil sites under TWW irrigation, the highest increases in IQI-TDS and NQI-TDS values were related to sites 2 and 4 where the highest increases were observed in the values of P, OM, and K versus the control.…”
Section: Tds Methodssupporting
confidence: 93%
“…This is associated with an upsurged soil quality grade from IV to III in most soil sites treated by TWW irrigation (Figure 2), indicating a positive effect of TWW irrigation on soil quality indices calculated by nutritional/chemical indicators. Our results corroborate the findings of previous studies conducted by Chen et al [63] and Lyu and Chen [64], who found that SQI and soil health conditions were improved by TWW irrigation. Among different soil sites under TWW irrigation, the highest increases in IQI-TDS and NQI-TDS values were related to sites 2 and 4 where the highest increases were observed in the values of P, OM, and K versus the control.…”
Section: Tds Methodssupporting
confidence: 93%
“…Management could be the main reason that caused the differences of soil nutrients among the different green space types [35,36]. On the one hand, it is well known that the PARK and ATTACH soils could get better fertilization and irrigation management, especially in classical imperial gardens which were constructed in Qing Dynasty [37]. Large amounts of high quality (rich in C and N) litter were produced by dry branches and fallen leaves from deciduous broad leaved trees, which then were broken down into humus, leading to increases in soil organic matter and nitrogen content [38].…”
Section: Discussionmentioning
confidence: 99%
“…Water samples were taken from June to August 2016 with an approximate interval of two weeks according to phonological stage of rice crop. 14 [32] were calculated. Values obtained from each water resource were treated as replicates.…”
Section: Water Quality Assessmentmentioning
confidence: 99%